The right to communication as a newly achieved human right - Jeftić Nevenka (Međunarodni Problemi, 2008)
Information technologies, free flow of information, free media and the right to communication are the pillars communicative sovereignty springs up from, relying upon them, too. This was the 20th century creation but it has been globally and more fully realized in the 21st century. Civilization openness and acceptance ability are the key categories for prosperity of communicative sovereignty.